Penggunaan Media Sosial Instagram Pandawara Group (@pandawaragroup) Sebagai Media Komunikasi Program Kerja Ajaraksa Pada Siswa SMPN 13 Bandung - Manurung, Normanela Tassel Epaphras; Wijaksono, Dimas Satrio (eProceedings of Management, 2024)
This research aims to look at the use of the Pandawara Group Instagram social media (@pandawaragroup) as acommunication medium for the Ajaraksa work program for SMPN 13 Bandung students. There are two views held byPierre Levy, namely the view of social interaction and social integration. This research was conducted using aqualitative approach method where there were subjects as informants, namely four key informants, one supportinginformant, and one expert informant. The data collection method will be in the form of interviews with informants inthe form of subjects, observations, and also followed by documentation in interview activities and also observations.The validity of the data depends on the source triangulation technique. The research results show that the view ofsocial interaction using social media Instagram @pandawaragroup is quite effective but can add information fromuploaded videos. Meanwhile, from a social integration perspective, the use of Instagram social media is quite effective. Keywords-Pandawara Group, Ajaraksa, Instagram, social interaction, social integration.